Teaching the Reformations - Christopher Metress (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
In October 2016, Samford University hosted Teaching the Reformations, a conference designed to help non-specialists teach the rich intellectual traditions of the Protestant and Catholic reformations more effectively in undergraduate core and general education courses. This volume includes keynote addresses by R. Ward Holder (St. Anselm College) and G. Sujin Pak (Duke Divinity School), as well as a selection of top papers from the conference.